Society for the Phenomenology of Religious Experience (Society for the Phenomenology of Religious Experience, 2002)
“The Society for Phenomenology of Religious Experience (SOPHERE) is a membership-supported international organization for philosophical phenomenological reflection on religious experience, as such reflection is related to philosophy itself, as well as to theology, and social and clinical sciences and practices. While our approach is grounded in continental philosophy, that is, the work of Husserl, Heidegger, Herring, Wahl, Marion, Merleau-Ponty, Stein, Fink, Henry, Levinas, and other early and contemporary phenomenological philosophers, we also welcome interdisciplinary reflection"